Thermochemical reduction modeling in a high-temperature moving-bed reactor for energy storage: 1D model. (15th January 2022) - Huang, Wei; Korba, David; Randhir, Kelvin; Petrasch, Joerg; Klausner, James; AuYeung, Nick; Li, Like
Highlights: A comprehensive 1D model for thermochemical reactors was developed. Model validation was conducted for stationary packed-bed and moving-bed reactors. The power components during transient and steady states were recorded. Predicted thermal input-to-chemical conversion efficiency ∼95%. Predicted reactor system solar fuel production efficiency ∼30%. Abstract: The design of robust and efficient high-temperature thermochemical reactors and determination of operating conditions are critical steps toward enabling high-efficiency long-duration solar energy storage. This work presents a computational model for the thermal reduction of a metal oxide material (Mg-Mn-O) up to 1450 °C and the coupled complex transport phenomena in a novel tubular thermal reactor design that features the capability for a high extent-of-reduction (high energy storage density) and inherent heat recuperation. A one-dimensional model coupling counter-current gas–solid flow, two-phase heat transfer, thermochemical redox reactions, and species transport in a moving-bed reactor is developed. Simplified versions of the model are validated with published results in the literature for packed beds with both inert and reactive particles; the fully coupled model is also validated with experimental measurements of a moving-bed reactor in terms of local temperatures and oxygen release at the exit. Detailed comparisons on the effects of different boundary conditions in the reaction zone (prescribed wall temperature vs. heat flux conditions) and formulations based on a simple uniform flow assumption vs. plug flow using Ergun equation for gas flow are investigated. The results are compared with experimental measurements, and for all cases, the energy flow components in the reactor system and the thermal to chemical conversion efficiency and overall system efficiency are computed. The predicted high thermal-to-chemical efficiency ∼95% and system efficiency ∼30% agree with experimental measurements.